Effect of protective bed composition on deactivation of a hydrotreating catalyst. Issue 3 (9th November 2021) - Yunusov, Mirakhmad P; Teshabaev, Zafar A; Mirzaeva, Elena I; Nasullaev, Khikmatullo A; Ergashev, Makhmudjon M; Ruzimuradov, Olim N; Murzin, Dmitry Yu
Abstract: BACKGROUND: The relationship between the chemical composition, texture, and the shape of the granules of the protective bed upstream hydrotreating, that influences the degree of metal removal from the residual vacuum gas oil, is a critical issue in oil refining. RESULTS: The character of the metal and sulphur distribution on the surface and in the volume of granules of the protective beds was studied for the model mixtures enriched with typical compounds deactivating hydrodesulphurization catalysts. The protective bed was operated along with the demetallization catalyst synthesized using local mineral raw materials (e.g., Angren high‐quality enriched kaolin) and production wastes (spent alumina sorbent from Shurtan gas chemical complex). CONCLUSION: It is shown, the use of a two‐bed protective system most effectively extended the life‐time of the main hydrotreating catalyst. The spent and deactivated Al‐Co‐Mo catalyst can be efficiently used in the synthesis of the catalyst used for the pre‐cleaning upstream hydrotreating. © 2021 Society of Chemical Industry (SCI).